POTENTIALS, CHALLENGES AND PROSPECTS OF HALAL TOURISM DEVELOPMENT IN ETHIOPIA - Ahmed, Mohammed Jemal; Akbaba, Atilla ([S.l.] : ROUTLEDGE, 2023)
This book explores the potential of halal tourism development and its implementation in Ethiopia. The insights presented assist key stakeholders to make informed decisions concerning commercial strategy, profitability and feasibility of halal tourism from the secular perspective. This innovative book offers a unique contribution to halal tourism, being the first of its kind to assess halal tourism development in developing countries. It provides a clear understanding of what halal tourism means, how it has evolved and the current status of the industry. The book considers the prospects of halal tourism, including the conceptual and practical challenges of halal tourism development. The example of halal tourism in Ethiopia is explored to provide a lens through which deeper understandings can be drawn on where and how to develop halal tourism This book will be of interest to, researchers, students in the disciplines of tourism, anthropology, geography, business administration and sociology. It also provides useful insights for policy makers, planners and professionals in the hospitality and tourism industry.
Keywords: Tourism -- Religious aspects -- Islam; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism